2021
DOI: 10.1039/d0cb00215a
|View full text |Cite
|
Sign up to set email alerts
|

Chemical methods for protein site-specific ubiquitination

Abstract: Chemical methods for protein site-specific ubiquitination are important for the understanding of Ub signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 133 publications
(188 reference statements)
0
24
0
Order By: Relevance
“…In this strategy, the protein of interest is recombinantly expressed with Cys mutation at the desired modification site to allow chemoselective transfer of electrophilic PTM precursors. These approaches enable direct protein functionalization with “small” PTMs such as mono-/di-/trimethylation [ 47 ], succinylation [ 55 ], glycosylation [ 46 ], acetylation [ 56 ] marks, and large complex analogs (e.g., ubiquitylation and sumoylation) [ 57 ].…”
Section: Late-stage Cys Functionalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this strategy, the protein of interest is recombinantly expressed with Cys mutation at the desired modification site to allow chemoselective transfer of electrophilic PTM precursors. These approaches enable direct protein functionalization with “small” PTMs such as mono-/di-/trimethylation [ 47 ], succinylation [ 55 ], glycosylation [ 46 ], acetylation [ 56 ] marks, and large complex analogs (e.g., ubiquitylation and sumoylation) [ 57 ].…”
Section: Late-stage Cys Functionalizationmentioning
confidence: 99%
“…Recently, this method was expanded to transfer large and complex PTMs into recombinant proteins [ 61 , 62 ]. In this regard, several novel synthetic approaches were developed to install Ub unit into the protein of interest with high fidelity [ 57 ]. For example, early reports showed that Ub units could be connected to the target protein via a disulfide linkage ( Figure 3 A) [ 63 , 64 ].…”
Section: Late-stage Cys Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A more challenging lysine PTM is site-specific ubiquitination. [130] Chemical synthesis of branched ubiquitin chains in native L-form is well reported, employing a removable glycyl auxiliary onto the lysine side chain (Figure 11A). [28,43,131] The auxiliary facilitates NCL with a ubiquitin thioester, following subsequent removal with TFA to generate a native glycine at the branched ligation site.…”
Section: Post-translational Modificationsmentioning
confidence: 99%
“…Ubiquitination is the covalent attachment of ubiquitin (Ub) or polyubiquitin (polyUb) chains to the Lys ε-amino group of a target protein. Several synthesis strategies have been used for the generation of (poly-)ubiquitin and its installation on target proteins, 92 but we focus here on Ub attachment combined with NMR spectroscopic analysis. The repetitive nature of polyUb molecules makes it almost impossible to resolve the respective NMR signals from individual subunits, which remained a challenge until 2011.…”
Section: Rsc Chemical Biology Accepted Manuscriptmentioning
confidence: 99%